Child labour & human rights a social dimension - Kaushal, Lata. (New Delhi : MD Publications Pvt Ltd., 2009)
With special reference to India.
Includes index.
Bibliography: p. [327]-332.
Keywords: Child labor -- India; Child labor; Children's rights -- India; Children's rights; Child labor -- Government policy -- India; Child labor -- Government policy